RELATIONSHIP BETWEEN THE ROLE OF WOMEN FARMER GROUP AND FARMER CHARACTERISTICS WITH MEMBER INCOME (CASE OF SRI KANDI WOMEN FARMER GROUP IN SUKRA DISTRICT, INDRAMAYU REGENCY) - Elsha Munziah; Hepi Hapsari; Tuti Karyani; Ahmad Choibar Tridakusumah (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
The ability of women's dual role in rural areas to increase income is carried out by processing agricultural products into food products, but business sustainability is still low. The government is here to assist its development through empowering women in the Women Farmers Group with the SIMURP (Strategic Irrigation Modernization and Urgent Rehabilitation Project) program, through product development and expansion of marketing reach. and the role of KWT with member income. This study uses a quantitative research design with a correlational approach conducted in Sukra District, Indramayu Regency in October 2022. The analysis used is descriptive analysis, KWT business income analysis, farmer group role analysis and Kendal tau correlation analysis. The results showed that the role of KWT Sri Kandi was included in the category of very instrumental. The age and role of KWT variables were significantly related to the income of KWT members and the variables of formal education level, non-formal education, and experience in joining farmer groups were not significantly related to the income of KWT members.